The Persistent Segregation of Girls into Lower-Paying Jobs while in School - Peter Kooreman (Institute for the Study of Labor (IZA), 2005)
This paper analyzes gender differences in jobs while in high school. The availability of school class based samples with detailed information on teenage jobs allows for a comparison of the behavior of boys and girls who are in the same school class, and thus have virtually identical education levels. Even within these highly homogeneous groups, boys earn substantially more than girls. The earnings gap cannot be explained by differences in participation rates and hours of work, nor by gender wage gaps within job types. It is entirely due to the fact that girls work more in job types with relatively low wages, in particular babysitting. During the period considered, 1984-2001, the gender patterns of jobs while in school largely remained unchanged.
Keywords: J16; J22; 330; labor market; gender differences; teenage behavior